Open-air shrine in Worli village - Mumbai Archive Project Team (Jio Institute, 2024)
The village is dotted with chapels, shrines, and Christian icons erected by residents. This open-air shrine, decorated with colourful ceramic tiles, was erected on 21 May 1954. It was built by Srimati Maribai Shanwar Satbhut and Shravanibai in memory of her deceased husband, Paskou Satbhut.